A CRITICAL DISCOURSE ANALYSIS OF THE KURDISH QUESTION WITH FOCUS ON THE DENIAL STRATEGIES - ALI , DONYA ABDULLAH; EBRAHIM, HALLAT RAJAB (Journal of Duhok University, 2023)
This study aims to explore how the denial of the Kurdish question operates in the Iraqi Kurds’ and Arabs’ personal experience narratives. To put it simply, this study explores the forms and functions of this denial in the personal experience narratives told by the Iraqi Kurds and Arabs within the framework of Critical Discourse Analysis (CDA). Using open-ended interviews, forty personal experience narratives (20 by Kurds and 20 by Arabs) were elicited as the data sample for this study. This study follows a qualitative paradigm in analyzing the data sample. In view of that, van Dijk’s (1992) model of denial has been used. The model consists of eight forms and four functions of denial. The application of van Dijk’s model to the selected data has yielded some conclusions: The study’s participants (Kurds and Arabs) have used different forms of denial in their personal experience narratives namely; disclaimers, transfer, mitigations, justification, excused, provocation (blaming the victim), and reversal. By using these forms of denial, Iraqi Arab speakers could present themselves positively and save their self-image at the same time. Conversely, Kurdish speakers sometimes used denial strategies as a “counter-attack” device to blame the other group (Iraqi Arabs) for denying their rights of having their own state. This study has also explored three functions of denial namely; individual, social, and cultural. The participants of both groups (Kurds and Arabs) rely on their individual, cultural, and social backgrounds to refer to their ideologies using denial strategies.